Perbedaan Volume Perdagangan Saham Dan Abnormal Return Saham Sebelum Dan Sesudah Peristiwa Pemecahan Saham (Stock Split) Pada Perusahaan Di Bursa Efek Indonesia - Ginting, Selaras Christiani; Rahyuda, Henny (E-Jurnal Manajemen, 2014)
The aim of this study is to analyze the significant differences of trading volume activity and abnormal return before and after stock split. This research performed on 19 companies which doing the stock split within 2008 up to 2012 in Indonesia Stock Exchange chosen by purposive sampling method. The analysis technique used is Paired Sample T - Test within event period 5 days before and after stock split. Based on result, show that there are significant differences between trading volume activity before and after stock split and there is no significant difference in the acquisition abnormal return before and after stock split.